Analysis of Chinese investment in renewable energy generation in Brazil - Zeng, Fenyu; Wu, HongZhen (Frontiers in Energy Research, 2024)
As a result of the "Belt and Road" and "Going Global" policies, a growing number of Chinese power companies are expanding overseas, implementing global development strategies, and making investments in the overseas power industry.Several countries are undergoing an energy transition because of the rapid development of the world economy. This is being done to address the climate change issues that are a result of the overuse of fossil fuels. Brazil is also accelerating its pace of power transformation in its position as a major power generating country in Latin America. In addition to being the largest economy in South America, Brazil is also the country in which China has made the most investments. Additionally, Brazil is increasing its development efforts in wind power, photovoltaics, and other renewable energy sources in response to a large demand for renewable energy sources. Brazil's renewable energy sector offers a great deal of potential for investment based on solid foundations for cooperation between China and Brazil. The Grey Prediction Model was used for this research to forecast Brazil's renewable energy generation installed capacity, and the results show a positive trend in Brazil's renewable energy generation.There is a rapid growth in wind and photovoltaic power generation over the next five years, with growth rates reaching 50.39% and 182.99%, respectively, suggesting that there is potential for a broad range of development. Following this, the research applies factor analysis to assess investment risks associated with Brazil's renewable energy sector from 2000 to 2020. Based on the results of the study, Chinese power companies investing in Brazil's renewable energy sector face the greatest political risk, while other risks gradually decrease. To avoid political risks when investing, companies should place a high priority on preventing them.China and Brazil represent the largest emerging markets in the Eastern and Western Hemispheres, respectively. The strategic partnership between China and Brazil is celebrating its 30th anniversary this year. A meeting between President Xi Jinping and the Brazilian President Luiz Inácio Lula da Silva on April 14, 2023, emphasized the need for China and Brazil to strengthen practical cooperation,